2017
DOI: 10.3390/ijerph14101208
|View full text |Cite
|
Sign up to set email alerts
|

Association of Waist Circumference Gain and Incident Prediabetes Defined by Fasting Glucose: A Seven-Year Longitudinal Study in Beijing, China

Abstract: The risk of incident prediabetes with gain in waist circumference (WC) has not been addressed among Chinese adults. A total of 7951 participants who underwent health check-ups at the Beijing Physical Examination Center and Beijing Xiaotangshan hospital were recruited in 2009 and followed up in 2016. Participants were classified into four groups according to categories of percent WC gain: ≤−2.5%, −2.5–2.5%, 2.5–5%, and >5%. The effect of WC gain on prediabetes was evaluated using modified Poisson regression mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
6
4
0
Order By: Relevance
“…The study of Manju Bala [26] found that WHR is positively correlated with HbA1c, which means that a decrease in WHR is effective for the prevention of prediabetes. The previous ndings regarding the association between the WHR and prediabetes [27,28] were consistent with the results of our study.…”
Section: The Ability Of Whtr Bmi Wc and Whr To Predict Prediabetes supporting
confidence: 93%
“…The study of Manju Bala [26] found that WHR is positively correlated with HbA1c, which means that a decrease in WHR is effective for the prevention of prediabetes. The previous ndings regarding the association between the WHR and prediabetes [27,28] were consistent with the results of our study.…”
Section: The Ability Of Whtr Bmi Wc and Whr To Predict Prediabetes supporting
confidence: 93%
“…Another study from Indonesia revealed that WtHR predicts prediabetes [39]. Another study from Chinese population showed that the risk of prediabetes increased significantly with increasing WC for both genders [14].…”
Section: Discussionmentioning
confidence: 97%
“…e distribution of fat in the body is measured by using simple, most practical, at a low cost, and widely used markers of obesity index like anthropometric measurements, such as body mass index (BMI), waist circumference (WC), waistto-hip ratio (WHR), and waist-to-height ratio (WHtR) [7,8]. Different previous studies showed varied prediction abilities of anthropometric measurements to predict prediabetes and diabetes [9][10][11][12][13][14][15][16][17][18][19][20][21]. A study conducted in Ethiopia indicated that WC was a predictor of CVD risk [22].…”
Section: Introductionmentioning
confidence: 99%
“…According to a 10-year cohort analysis of office workers in large corporations [ 3 ], the OR of those who worked for over 20 years, compared to those who worked 1 to 2 years, were 2.70 (95% CI = 1.63–4.45) in waist circumference (male ≥90 cm), and the risk of contracting diabetes was 3.7 times, which was the highest. In addition, previous studies [ 28 , 37 ] reported that it was important to monitor and prevent increases in waist circumference to reduce the increasing burden of prediabetes, diabetes, and its complications. These are similar to the results of the present study and highlight the need for further studies to consider working years and maintaining waist circumference.…”
Section: Discussionmentioning
confidence: 99%
“…To identify the influencing factors of prediabetic state, stepwise multiple logistic regression was performed using regression models. Among the statistically significant variables in the descriptive statistical analysis and risk analysis, working years, marital status, waist circumference, systolic blood pressure, and diastolic blood pressure were included to perform multiple logistic regression, but age, body weight, and BMI were excluded, since working years were highly correlated with age and waist circumference were highly related with body weight and BMI, and working years and waist circumference were important factors for office workers [ 3 , 28 ].…”
Section: Methodsmentioning
confidence: 99%